IMPLEMENTASI GOOD CORPORATE GOVERNANCE DALAM PELAKSANAAN DANA DESA (STUDI KASUS DI DESA UJUNG-UJUNG, KECAMATAN PABELAN, KABUPATEN SEMARANG) - Dian Alluwina Putri Sejati; Winena Renidya Faradena (Prosiding Seminar Nasional Akuntansi dan Manajemen (SENAMA), 2018)
This study aims to explain the process of managing the Village Fund Allocation and can explain how to apply the principles of good governance in the process of managing Village Fund Allocation, especially in Ujung-ujung village, Pabelan District, Semarang Regency, Central Java. This research is expected to have an impact on the management of Village Fund Allocation which is increasingly effective and efficient and can reduce the potential for fraud through the use of good governance principles. This study uses a qualitative approach. Data collection is done through interviews, observations and documentary studies. The results of this study indicate that the implementation of village funds in the village of Ujung-ujung, Pabelan District, Semarang Regency, Central Java as a whole has been in accordance with Permendagri No. 113 of 2014, even though the villages at the end still have obstacles in administration.